PRAKTIK PENGENALAN DAN KEMAMPUAN SCUBA DIVING BAGI MAHASISWA DAN MAHASISWI KEDOKTERAN UNIVERSITAS NEGERI PAPUA - Tjarles Lay; M. Ali Ulat; Vicky Rizky Affandi Katili; Anthon Apolus Orisu (Politeknik Kelautan dan Perikanan Sorong, 2022)
Scuba diving is a high-risk sport if it is not carried out according to the correct procedure. Scuba diving can be done with various needs, both personal or professional reasons. The purpose of implementing the introduction and ability of scuba diving practice is to get to know scuba diving equipment, to know the function of each tool, to know how to install and remove equipment and to dive. The practice participants were 16 people from the medical faculty of the State University of Papua. The method used is lecture/short material, demonstration and drill/practice. The results of the practice participants are able to recognize and use basic diving equipment (masks, snorkels and fins) and scuba equipment.